Identification and Bioactivities of Secondary Metabolites Derived from Endophytic Fungi Isolated from Ethnomedicinal Plants of Tujia in Hubei Province: A Review - Ye, Ke (Nat Prod Bioprospect, 2021)
Tujia is a national minority, inhabiting in the mountainous Wuling area in China. Since 1978, Tujia medicine has been studied, summarized and developed, leading to numerous achievements by Chinese researchers, such as the publishing of approximately 30 monographs of Tujia medicine. These publications are focused on summarizing and improving the theory of Tujia medicine and developing clinical therapies from this system of medicine. The shortage of natural medicinal plants used in Tujia medicine has created the need to discover new resources to replace them and protect endangered natural plant species. Endophytic fungi are one of the conservation options, are considered a source of new bioactive natural products, and are a renewable and inexhaustible source of new drugs and agrochemicals. This review summarizes 260 compounds from endophytic fungi that have been previously isolated from the medicinal plants of Tujia. These compounds include steroids, terpenoids, meroterpenoids, polyketides, alkaloids, peptides, aliphatic compounds, aromatic compounds, and heterocyclic compounds. [Image: see text]